Lifelong guidance policies in France and in Europe: where reforms are heading? - Borras, Isabelle (Grenoble, 2009)
"The transformations occurring in work and employment at the present time are raising new expectations with respect to guidance policies. Public action concerning guidance is challenged by the growing complexity of educational and professional pathways and increasing career mobility. To deal with these new expectations with concerning guidance, its steering system needs to be reformed. The aim of this survey is to describe the reforms underway in France. French specificities will also be revealed by comparison with examples from other countries based on a literature review."